Reckless opportunists : elites at the end of the establishment - Davis, Aeron (Manchester capitalism, 2018)
"Aeron Davis takes a close look at the state of elites today. He argues that the Brexit vote and 2017 election outcome are signs of a deeper leadership crisis that has been developing over decades. The great transformations of the 1980s onwards have not only upended societies, they have reshaped elite rule itself. Too many leaders today, regardless of intent, are ignorant, precarious, rootless and self-serving. Although richer, they have lost coherence, influence and control. Increasingly, they are just reckless opportunists, getting what they can amid the chaos they have created. Their failings are not only damaging wider society, they are undermining the very foundations of the Establishment itself. The book, based on interviews with over 350 elite figures, asks: how did we end up producing the leaders that got us here and what can we do about it?"--Publisher's description.